The Side Effects of Intracesarean Intrauterine Contraception: A Descriptive Study - Rumopa, Karol A; Wantania, John; Sondakh, Joice (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the side effects and acceptance of intracesarean Intrauterine Device (IUD) insertion. Methods: This was a descriptive study. Subjects were all pregnant women who had Cu T380A IUD to be placed after cesarean delivery at Prof. Dr. dr. R. D. Kandou Hospital during the period between August 2016 and September 2016. Results: A total of 52 subjects were recruited in this study.43 (82.69%) subjects were in the age group of 20-30 years. 51 of the subjects accepted the IUD. On the 7th day, 49 (94.23%) and 51 (98.07%) subjects complained of abdominal pain and vaginal bleeding, respectively, while on the 14th day, 48 (92.3%) and 50 (96.1%) subjects had abdominal pain and vaginal bleeding, respectively. There were significant decreases in both complaints on the 14th day, compared to the 7th day. (p<0.05 and p<0.05, respectively). 51 (98.07%) subjects accepted the IUD. There were no significant difference between acceptance on day 7 and 14th (p>0.05). Conclusion: The acceptance of side effects by the acceptor reaches 100%, with the incidence of early postpartum expulsion is 3.8%. The side effects of IUD are minimal. [Indones J Obstet Gynecol 2017; 5-3: 139-141] Keywords: intra-cesarean, intrauterine device, side effects